Kepuasan Kerja Dipengaruhi oleh Kompensasi, Motivasi dan Disiplin Kerja pada Karyawan PT.Wulandari Bangun Laksana Tbk - Faradilla Amalia Putri; Didik Hadiyatno; Rahajeng Cahyaning Putri Cipto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to know the influence of Compensation, Motivation, and Work Discipline to Employee Job Satisfaction of PT Wulandari Bangun Laksana Tbk. The type of research used is quantitative research. The sampling technique in this research is purposive sampling with the sample taken is employees of PT Wulandari Bangun Laksana Tbk which amounted to 47 employees. Data collection method is done by distributing questionnaires. This research uses multiple linear regression with the help of SmartPLS in processing data. The result of this research shows that compensation, motivation, and work discipline have influence on job satisfaction of PT Wulandari Bangun Laksana Tbk employees.